Down-regulation of four arsenic antagonists on apoptosis and telomerase activity induced by arsenic trioxide in three myelocytic leukemia cell lines - Wei Ya-Ming; Ou Ying-Xian; Bai Hai; Lu Ji-Hong; Zheng Rong-Liang (Acta Pharmacologica Sinica; Vol 22, No 8 (August 2001): Acta Pharmacologica Sinica, 2016)
Aim: To investigate regulative effects of thiol reagents, N-acetyl-l-cysteine (NAC) and natrii dimercaptosussinas (NDMS), catalase (CAT), and calcium chelator 2-[(2-bis-[carboxymethyl]-amino-5-methyl-phenoxy)-met]-6-methoxy-8-bis-[carboxy-methyl]-aminoquinoline (Quin 2) on apoptosis and telomerase activity induced by arsenic trioxide (As2O3) in three myelocytic leukemia cell lines. Methods: Flow cytometry was used to examine apoptosis and a PCR ELISA kit was used to detect telomerase activity. Results: As2O3 induced about 40 % - 60 % of apoptosis in NB4, K562, and HL-60 cells at the concentration of 0.6, 2.7, and 8.1 micromol/L respectively, as well as down-regulated telomerase activities in three cell lines. NAC 4 mmol/L, NDMS 200 micromol/L, CAT 80 kU/L, and Quin 2 20 micromol/L could down-regulate apoptosis variously induced by As2O3. NAC and CAT alone could decline telomerase activity in three cell lines and further decline telomerase activities that had been decreased by As2O3, whereas Quin 2 antagonized the decline in K562 and HL-60 cells. Conclusion: Thiol activity loss, free radical alteration, intracellular calcium changes, and decline of telomerase activity might be involved in As2O3-induced apoptosis. NAC, NDMS, CAT, and Quin 2 antagonized in some extent the effect of As2O3 on the three tested cell lines.